The second century of cinema : the past and future of the moving image - Dixon, Wheeler W., 1950- (Albany, N.Y. : State University of New York Press, 2000)
The author "explores the possible effects of the digital age on the production and exhibition of films."--Cover
Voices from the margins, and the new digital cinema -- Visions of the gothic and grotesque -- Images of conquest and the colonialist instinct -- The commodofication of desire, and the disruptive figure of Paul Robeson -- The past and the future of the moving image.
Includes bibliographical references (pages 247-260) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Motion pictures; Motion Pictures; Cinéma.; PERFORMING ARTS -- Film & Video -- Reference; Motion pictures; Filmkunst; Filmindustrie; Toekomstverwachtingen; Filosofische aspecten; Film; Music, Dance, Drama & Film; Motion pictures; Motion pictures; Films